A patient called Medical Research - Furst, Tomas; Strojil, Jan (Biomedical papers, 2017)
We report the case of a patient called Medical Research who presents with multiple life threatening symptoms, including a plethora of false positive results. This paper describes the course of the disease, discusses possible etiologies and offers options for future management to ensure the survival of the patient and that of our civilization.
Keywords: reproducibility crisis; perverse incentives; P value; publication bias; frequentist; Bayesian